2005
DOI: 10.1029/2004ja010596
|View full text |Cite
|
Sign up to set email alerts
|

Effect of strong thermalization on shock dynamical behavior

Abstract: [1] The dynamics of the perpendicular shock front is examined under various plasma parameters by using particle-in-cell numerical simulation. As widely accepted, above the critical Mach number ($3) the front of (quasi-)perpendicular shocks show nonstationary behavior due to the shock self-reformation. In much higher Mach number regime (M A > 20), we find that dynamics of the shock front self-reformation can be modified. Nonlinear evolution of microinstabilities in the shock transition region results turbulent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…They improved understandings of the process not only in terms of electron heating but also in terms of a production process of nonthermal electrons and promoted a number of subsequent simulation studies. [10][11][12][13][14][15][16][17][18][19][20][21][22] As a result, the understanding of electron heating or acceleration processes initiated by the BI in the context of the shock physics has been extensively developed.…”
Section: Introductionmentioning
confidence: 99%
“…They improved understandings of the process not only in terms of electron heating but also in terms of a production process of nonthermal electrons and promoted a number of subsequent simulation studies. [10][11][12][13][14][15][16][17][18][19][20][21][22] As a result, the understanding of electron heating or acceleration processes initiated by the BI in the context of the shock physics has been extensively developed.…”
Section: Introductionmentioning
confidence: 99%
“…It has been recognized for a long time that a variety of microinstabilities play a crucial role in wave excitation, particle heating, and anomalous dissipation mechanisms in the shock transition region [see, e.g., Papadopoulos , 1985, and references therein]. Indeed, recent full particle simulation studies revealed that a variety of microinstabilities are generated in the foot of low beta supercritical quasi‐perpendicular shocks [e.g., Shimada and Hoshino , 2000; Dieckmann et al , 2000; Hoshino and Shimada , 2002; Scholer et al , 2003; Matsukiyo and Scholer , 2003; Shimada and Hoshino , 2004; Scholer and Matsukiyo , 2004; Shimada and Hoshino , 2005; Muschietti and Lembège , 2006]. The free energy source of those microinstabilities are the relative drift between incoming electrons and reflected ions and incoming electrons and incoming ions, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, in Matsukiyo and Scholer 's [2006] PIC simulation for the foot region, whistler waves did exist. Shimada and Hoshino [2004, 2005] have also shown, using PIC simulation, ion phase space holes due to wave‐particles interaction when ω pe /Ω ce is large, which implies that the generation of electromagnetic waves in the foot and ramp region should be possible.…”
Section: Simulation Resultsmentioning
confidence: 98%